The Importance Of Enterpreneurship Counseling For Rehabilitation Patients In The National Narcotics Agency Of West Java - et. al., Yana Hendayana, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The degree of knowledge and understanding in entrepreneurship for the rehabilitation patients in the National Narcotics Agency of West Java is still lacking, thereby counseling about entrepreneurship, training, and education regarding Hydroponic entrepreneurship is needed. Hydroponics is a method of growing plants without soil and only using water. The water used for growing the plants is also more efficient, not as much as if you plant it in conventional ways. This counseling aimed to help the government develop entrepreneurship in Indonesia, especially for the younger generations in rehabilitation within the National Narcotics Agency of West Java. Rehabilitation in the National Narcotics Agency stated that the implementation of Indonesian National Standards must consistent, so the rehabilitation process for the NPAS addicts, the abusers, and the victims of abuse is managed optimally. As stated in Article 54 of Law number 35, the Year 2009 about Narcotics, drug addicts, and drug abuse victims are obliged to undergo medical rehabilitation and social rehabilitation. This counseling session was held in collaboration between Widyatama University and the National Narcotics Agency of West Java on February 15th - 20th, 2021. Eighty people were participating in this session. Results obtained from this Community Service Activity are that participants can practice and develop their counseling output.